THE QUESTION OF REPARATIONS IN THE CONTEXT OF ANGLO-GERMAN RELATIONS IN 1924 – 1929 - M. N. Sozonov (Вестник Кемеровского государственного университета, 2015)
The paper is devoted to the settlement of the question of reparations in the context of the relations between Germany and Britain in the second half of the 1920s. The paper aims at describing the main milestones in the solution of the problem of reparations and designating the reasons for the revision of the Dawes Plan. The paper also pays attention to the evolution of British and German policy in the reparations question, the role of particular political figures in its regulation. A conclusion is made about the combination of economical and political reasons for the revision of the Dawes Plan. For almost two years the British Government opposed that revision, hoping to force its position. Due to the pressure of the Allies on London and the beginning of Germany‘s economic difficulties, eventually Britain met Berlin and the Allies halfway.